Infodemic amidst the Covid-19 in the Philippines: Spotted By Vera Files.Org - Sabonsolin, John Cavin M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study analyzes the infodemic in the Philippines during the intense lockdowns during the early stages of the covid-19 pandemic. With the said lockdown, people are observed to be more present in social media. World Health Organization pronounced that "infodemic" poses a severe problem in public health. This article analyzes the fact-checked articles of Verafiles.Org, fact-checkers certified by non-partisan International Fact-Checking Network, during the first six months of covid-19 era. Using content analysis, the researcher examines the sources, claims, treatment, and access to the voice of Verafiles fact-checking articles. The researcher quantifies the variables and coded the data using the tables in order to obtain the findings of the study. Results show that most fact-checked "fake news" claims found in vera files.org are disinformation. It is also noted that Facebook and Youtube are the top platforms as a source of disinformation. The treatment of the fake information is usually done as facebook post or youtube video. It also found out that most of the claims are about Covid- 19 pandemic and political propaganda. Troll accounts, Facebook groups, pages, and websites supported Duterte, and even government officials listed as a source of "fake news."